Dynamic modeling and experimental investigation of a high temperature PEM fuel cell stack. (2nd March 2016) - Nguyen, Gia; Sahlin, Simon; Andreasen, Søren Juhl; Shaffer, Brendan; Brouwer, Jack
Abstract: High temperature polymer fuel cells operating at 100 to 200 ◦ C require simple fuel processing and produce high quality heat that can integrate well with domestic heating systems. Because the transportation of hydrogen is challenging, an alternative option is to reform natural gas on site. This article presents the development of a dynamic model and the comparison with experimental data from a high temperature proton exchange membrane fuel cell stack operating on hydrogen with carbon monoxide concentrations up to 0.8%, and temperatures from 155 to 175 ◦ C. The dynamic response of the fuel cell is investigated with simulated reformate gas. The dynamic response of the fuel cell stack was compared with a step change in current from 0.09 to 0.18 and back to 0.09 A/cm 2 . This article shows that the dynamic model calculates the voltage at steady state well. The dynamic response for a change in current shows that the model compares well with some of the cells in the stack while other cells may have typically lower voltages levels during dynamic operation. Highlights: A high temperature proton exchange membrane fuel cell dynamic model was developed. Data was acquired from a high temperature proton exchange membrane fuel cell. Performance with and without carbon monoxide up to 0.8% are well predicted. Dynamic responses of some cells to a step change in current are well predicted. Dynamic responses of the cells in the fuel cell stack varied significantly.